Bon and Naxi Manuscripts - Helman-Ważny, Agnieszka; Ramble, Charles (Studies in Manuscript Cultures, 2023)
This collective volume offers an insight into the Bon and Naxi manuscript cultures and their possible interconnections. This is the first primarily object-based study to deal with Bon and Naxi cultural history, book technology, collections of Bon and Naxi manuscripts, the relationship between text and image, writing materials, and the historical and archaeological context of the manuscripts' places of origin.